PARP inhibitor-induced torsades de pointes in long QT syndrome: a case report. Issue 1 (31st December 2019) - Segan, Louise; Beekman, Ashley; Parfrey, Shane; Perrin, Mark
Abstract: Background: Poly ADP-ribose polymerase (PARP) inhibitors target pathogenic BRCA mutations in chemotherapy-resistant malignancies. PARP inhibitors cause modest dose-dependent QT prolongation in the setting of a normal baseline QT interval. Case summary: We describe a case of PARP inhibitor-induced torsades de pointes (TdP) in an 86-year-old gentleman prescribed rucaparib due to chemotherapy-resistant, metastatic prostate cancer with pre-existing long QT, with an apparent dose-dependent increase in QT interval. The patient presented with syncope and recurrent TdP requiring direct cardioversion reversion (200 J biphasic) and an isoprenaline infusion (2 μg/min). There were no other QT prolonging agents and no electrolyte or metabolic disturbance to account for this arrhythmia. Improvement in QT interval was observed within 72 h of rucaparib cessation. Discussion: PARP inhibitors cause a modest, dose-dependent increase in QT interval in patients with a normal baseline. The safety of PARP inhibitors in patients with pre-existing long QT has not been evaluated. This is the first reported case of rucaparib-associated TdP in a patient with pre-existing long QT, highlighting the amplified effect of this agent in individuals with pre-existing QT prolongation and the risk of fatal arrhythmias.